Mediated Bordering : Eurosur, the Refugee Boat, and the Construction of an External EU Border - Ellebrecht, Sabrina (2020)
Long description: The external border of the EU remains under permanent construction. Sabrina Ellebrecht engages with two of its primary building sites - the European Border Surveillance System (Eurosur) and the Refugee Boat. She analyzes how the function and quality of the EU's current political border is crafted, shaped, produced and eventually stabilized through these two mediators. Eurosur and the Refugee Boat mediate a level of Europeanization which has hitherto - and would otherwise have - been impossible. While Eurosur mobilizes the limits of border policing in various ways, the Refugee Boat functions as the vacillating European Other to legitimize both control and humanitarian interventions. The study shows the specific, if not constitutive, ambivalences of EU border policies, and explores the emergence of viapolitics. - Biographical note: Sabrina Ellebrecht is a Senior Researcher in Sociology at the Centre for Security and Society at the University of Freiburg, Germany, where she currently leads the Mercator Foundation research group »The Police In An Open Society«. Her research interests lie in the fields of border and migration studies, political sociology, critical security studies, and police research. She was previously a visiting fellow at the DFG-Research Training Group »Topology of Technology« at the Technische Universität Darmstadt, and a visiting researcher the University of KwaZulu Natal in Durban, South Africa and the Jawaharlal Nehru University in New Delhi, India.